Affective and cognitive empathy in adolescents with autism spectrum disorder - Mazza, Monica; Pino, Maria C.; Mariano, Melania; Tempesta, Daniela; Ferrara, Michele; De Berardis, Domenico; Masedu, Francesco; Valenti, Marco (Frontiers in Human Neuroscience, 2014)
The broad construct of empathy incorporates both cognitive and affective dimensions. Recent evidence suggests that the subjects with Autistic Spectrum disorder (ASD) show a significant impairment in empathic ability. The aim of this study was to evaluate the cognitive and affective components of empathy in adolescents with ASD compared to controls. Fifteen adolescents with ASD and fifteen controls underwent paper and pencil measures and a computerized Multifaceted Empathy Test. All measures were divided into Mentalizing and Experience sharing abilities. Adolescents with ASD compared to controls showed deficits in all mentalizing measures: they were incapable of interpreting and understanding the mental and emotional states of other people. Instead, in the sharing experience measures, the adolescents with ASD were able to empathize with the emotional experience of other people when they express emotions with positive valence, but were not able to do so when the emotional valence is negative. These results were confirmed by the computerized task. In conclusion, our results suggest that adolescents with ASD show a difficulty in cognitive empathy, whereas the deficit in affective empathy is specific for the negative emotional valence.